2018
DOI: 10.31580/apss.v2i3.453
|View full text |Cite
|
Sign up to set email alerts
|

Online Food Delivery Service Quality: Does Personal Innovativeness Matter?

Abstract: The emergent of online food delivery (OFD) industry is valued as a new channel in food industry in order to grab more sales and shares and has promoted the competitiveness among the OFD players. Therefore, a sufficient understanding of the nature of the online service industry is very important for service providers in this emerging market. This study attempts to discover the characteristics and necessities of this online service. Using adapted questionnaire from M-S-QUAL (Huang et al., 2015), this study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Recent literature has shown that consumer service, experience, and WOM are related to each other in the context of food delivery applications (Kaur, Dhir, Ray, et al., 2020). A positive association was found between the quality of services and WOM in the online food delivery context (Yusra & Agus, 2018). WOM is directly proportional to consumer satisfaction.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Recent literature has shown that consumer service, experience, and WOM are related to each other in the context of food delivery applications (Kaur, Dhir, Ray, et al., 2020). A positive association was found between the quality of services and WOM in the online food delivery context (Yusra & Agus, 2018). WOM is directly proportional to consumer satisfaction.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…In addition to this, moral values could act as a barrier for OFD continuance. Yusra and Agus (2018) found that, while satisfaction mediates the quality of service and customer loyalty, personal innovativeness of customers influenced their faith and delight. Correa et al (2018) suggested that transaction volumes and timely deliveries were not associated with traffic.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…In context of OFDAs, there is insufficient research on consumer behaviour and prior literature depicts that the available studies have primarily employed the technology acceptance models, including UTAUT2 (Alalwan, 2020;, UTAUT (Okumus et al, 2018), Extended Information Technology Continuance Model (Yeo et al, 2017), and electronic-service quality framework (Sjahroeddin, 2018;Suhartanto et al, 2019;Yusra & Agus, 2018).…”
Section: Introductionmentioning
confidence: 99%